THE IMAGE OF A NOBLEMAN IN „NAPIS NA GROBIE… GREHORA CHODKIEWICA" (INSCRIPTION ON THE TOMB OF... GREHOR CHODKIEWIC) BY MACIEJ STRYJKOWSKI - Mieszek, Małgorzata (Prace Polonistyczne, 2025)
The article examines the literary portrayal of Grehory Chodkiewic in Maciej Stryjkowski’s Napis na grobie (Inscription on the Tomb). Chodkiewic is depicted in line with the conventions of a panegyric. While Stryjkowski employs typical epicedial clichés, he also enriches these patterns with epic narratives detailing Grehory’s achievements. Additionally, he makes skilful use of exaggeration to emphasize Grehory’s greatness. As a result, Stryjkowski crafts an image that aligns with the literary preferences and aesthetic standards of noble audiences of the time.